2013
DOI: 10.1093/ejcts/ezt545
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of rivaroxaban for thromboprophylaxis of prosthetic heart valves in a porcine heterotopic valve model

Abstract: In this study, rivaroxaban was more effective than enoxaparin for short-term thromboprophylaxis of mechanical valve prosthetics in the heterotopic aortic position. It reduced valve thrombus and platelet deposition on day 30 following implantation without increased adverse events. Future studies would provide additional support for clinical trials evaluating rivaroxaban as an alternative to warfarin for appropriately selected patients with prosthetic aortic valves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 26 publications
(33 reference statements)
0
20
0
Order By: Relevance
“…In vitro and animal models have shown promising results in the efficacy of rivaroxaban as thromboprophylaxis in MHV [ 27 , 28 ]. Recently, we reported promising results from the first experience of a Factor Xa inhibitor (rivaroxaban) in humans, where we followed seven patients with MHV over 3 months [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and animal models have shown promising results in the efficacy of rivaroxaban as thromboprophylaxis in MHV [ 27 , 28 ]. Recently, we reported promising results from the first experience of a Factor Xa inhibitor (rivaroxaban) in humans, where we followed seven patients with MHV over 3 months [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while the prohibition of dabigatrin was expanded to the general class of NOACs, no current clinical data regarding the fXa inhibitors has been published. In fact there is early evidence that rivaroxaban is more effective than enoxaparin at preventing porcine thrombosis [25]. Yet this must be considered preliminary and it is not known at this point in time whether either rivaroxaban or apixaban is protective and different from dabigatrin.…”
Section: Issn: 2476-230xmentioning
confidence: 99%
“…47 Similar findings were made in an earlier animal study that suggested that rivaroxaban might be superior to standard therapy after mechanical valve surgery in terms of valve thrombus and platelet deposition. 48 Unexpected results came also from the Re-Align study, that aimed to investigate dabigatran in patients after mechanical heart valve surgery. Increased rates of thromboembolic and bleeding complications compared with VKA regimen were observed.…”
Section: Factor Xa Inhibitorsmentioning
confidence: 99%